2020
DOI: 10.1177/1687814020985267
|View full text |Cite
|
Sign up to set email alerts
|

Forced convective heat transfer and thermal efficiency assessment in square channel equipped with 10° wavy thin rib

Abstract: Forced convective heat transfer and thermo-hydraulic efficiency in the heat exchanger square channel (HESC) inserted with 10° wavy thin rib (WTR) are reported numerically. The effects of rib height, pitch distance and flow velocity on flow and heat transfer profiles are considered. The rib height to the channel height; e/H or HR, is varied in the range 0.05–0.30, while the rib pitch to the channel height; P/H or PR, is varied in the range 0.50–1.25. The air velocity in the HESC inserted with the WTR is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In addition, the maximum TEF of 4.06 is found at Re = 2,000, b/H = 0:10, and s/H = 0:05 for the VU direction (see Figure 15). The comparison between the numerical results from this present study and those from previous works [24][25][26][27] is shown in Figure 16. Figure 16(a) shows that the present vortex generator provides lower heat transfer rate than the V-orifice [27].…”
Section: Modelling and Simulation In Engineeringmentioning
confidence: 57%
“…In addition, the maximum TEF of 4.06 is found at Re = 2,000, b/H = 0:10, and s/H = 0:05 for the VU direction (see Figure 15). The comparison between the numerical results from this present study and those from previous works [24][25][26][27] is shown in Figure 16. Figure 16(a) shows that the present vortex generator provides lower heat transfer rate than the V-orifice [27].…”
Section: Modelling and Simulation In Engineeringmentioning
confidence: 57%
“…The methodology of the present work is referred from Reference [20]. The fluid flow and heat transfer in the HESC are assumed to be steady in three dimensions.…”
Section: Mathematical Foundation and Initial And Boundary Conditionsmentioning
confidence: 99%